CHELATE COMPLEXES BASED ON ACRYLAMIDE MONOMETHILOL (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Formation of complex acetates of metal ions Co2+, Mn2+, Cd2+ and monomethilolakrilamidom has been studied. By methods of IR, NMR spectroscopy and element analysis composition and structure of the rough formed chelate complexes are investigated. By measuring the magnetic moments are defined, which made it possible to determine also the coordination numbers of metal ions in the appropriate complexes.
Keywords: acetates of metal ions; magnetic moments; chelate complexes